Δ133p53α enhances metabolic and cellular fitness of TCR-engineered T cells and promotes superior antitumor immunity - Legscha, Kevin Jan; Ferreira, Edite Antunes; Chamoun, Antonios; Lang, Alexander; Awwad, Mohamed; Ton, Gigi Nu Hoang Quy; Galetzka, Danuta; Guezguez, Borhane; Hundemer, Michael; Bourdon, Jean-Christophe; Munder, Markus; Theobald, Matthias; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background Tumor microenvironment-associated T cell senescence is a key limiting factor for durable effective cancer immunotherapy. A few studies have demonstrated the critical role of the tumor suppressor TP53-derived p53 isoforms in cellular senescence process of non-immune cells. However, their role in lymphocytes, in particular tumor-antigen (TA) specific T cells remain largely unexplored. - Methods Human T cells from peripheral blood were retrovirally engineered to coexpress a TA-specific T cell receptor and the Δ133p53α-isoform, and characterized for their cellular phenotype, metabolic profile and effector functions. - Results Phenotypic analysis of Δ133p53α-modified T cells revealed a marked reduction of the T-cell inhibitory molecules (ie, CD160 and TIGIT), a lower frequency of senescent-like CD57+ and CD160+ CD8+ T cell populations, and an increased number of less differentiated CD28+ T cells. Consistently, we demonstrated changes in the cellular metabolic program toward a quiescent T cell state. On a functional level, Δ133p53α-expressing T cells acquired a long-term proliferative capacity, showed superior cytokine secretion and enhanced tumor-specific killing in vitro and in mouse tumor model. Finally, we demonstrated the capacity of Δ133p53α to restore the antitumor response of senescent T cells isolated from multiple myeloma patients. - Conclusion This study uncovered a broad effect of Δ133p53α isoform in regulating T lymphocyte function. Enhancing fitness and effector functions of senescent T cells by modulation of p53 isoforms could be exploited for future translational research to improve cancer immunotherapy and immunosenescence-related diseases.
Gesehen am 04.11.2021